2014
DOI: 10.1038/nmeth.3014
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of quantitative miRNA expression platforms in the microRNA quality control (miRQC) study

Abstract: MicroRNAs are important negative regulators of protein-coding gene expression and have been studied intensively over the past years. Several measurement platforms have been developed to determine relative miRNA abundance in biological samples using different technologies such as small RNA sequencing, reverse transcription-quantitative PCR (RT-qPCR) and (microarray) hybridization. In this study, we systematically compared 12 commercially available platforms for analysis of microRNA expression. We measured an id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
534
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 565 publications
(570 citation statements)
references
References 17 publications
17
534
2
5
Order By: Relevance
“…To characterize miRNA signatures in the plasma of AA, the Serum/Plasma Focus microRNA PCR Panel was used, as it is considered optimal in terms of reproducibility, sensitivity, accuracy, and specificity. 27 We found that circulating miRNAs were differentially expressed in AA and MDS vs. HC and in AA vs. MDS, which was validated in a larger separate cohort using a different normalization method. By multivariate analysis, we identified the 5 miRNAs (miR-150-5p, miR-146-5p, miR-1, miR-22-3p, and miR-424-5p) that were significantly associated with AA or MDS, and these miRNA expression patterns were similar between the 2 cohorts.…”
Section: Discussionmentioning
confidence: 60%
“…To characterize miRNA signatures in the plasma of AA, the Serum/Plasma Focus microRNA PCR Panel was used, as it is considered optimal in terms of reproducibility, sensitivity, accuracy, and specificity. 27 We found that circulating miRNAs were differentially expressed in AA and MDS vs. HC and in AA vs. MDS, which was validated in a larger separate cohort using a different normalization method. By multivariate analysis, we identified the 5 miRNAs (miR-150-5p, miR-146-5p, miR-1, miR-22-3p, and miR-424-5p) that were significantly associated with AA or MDS, and these miRNA expression patterns were similar between the 2 cohorts.…”
Section: Discussionmentioning
confidence: 60%
“…8,9,11 Moreover, PCR-based systems require great care with primer design due to their target-based amplification, and often introduce sequence bias. 9,12 Microarrays, however, allow large-scale parallel detection of miRNAs, but usually require relatively long assay times with complicated steps. 9,13 Therefore, there is a great demand for systems that provide high sensitivity and specificity without target-based amplification, a simple workflow, and the ability to multiplex small panels of miRNAs in a high throughput manner.…”
mentioning
confidence: 99%
“…However, the NanoString platform uses a quantitative assay that has been validated in other studies. 31 We did not collect information on fathers and thus our study cannot address any effects of sperm or other paternal factors on cervical miRNA expression.…”
Section: Discussionmentioning
confidence: 99%